MILENIAL SISTEM PENYIRAMAN OTOMATIS DI PERKEBUNAN TOMAT MENGGUNAKAN ANDROID BERBASIS APLIKASI APP INVERTOR - Darmawan Bangun Prasetio; Rini Puji Astutik; Yoedo Ageng Surya (Power Elektronik : Jurnal Orang Elektro, 2023)
In today's life, we need something simple, fast and effective. Humans are required to be efficient in time in various things and activities. The agricultural sector is no exception. Difficulty in caring for and managing plants is one of the factors in the lack of greenery around community settlements. Water content and adjustment of soil contours also make maintenance difficult, because tomato plants have different water and humidity requirements for each type of plant. Tomato plantations are all activities that cultivate certain tomato plants on soil or other planting media in an appropriate ecosystem, to process and market goods and services produced from these plants, with the assistance of technology, capital and management to create prosperity for tomato plantation business actors. and society. Tomato plants are vegetables that we consume in this life and tomatoes can nourish our bodies. To produce quality tomato plants, good tomato plant maintenance is needed. The irrigation system that has been used so far is manual. Therefore, an automatic watering system was created using an Invertor-based Android application so that we can control watering and make it easier for tomato garden owners when they are out of town and then we can control it from Android and become more time efficient so that they can do other things.In today's life, we need something simple, fast and effective. Humans are required to be efficient in time in various things and activities. The agricultural sector is no exception. Difficulty in caring for and managing plants is one of the factors in the lack of greenery around community settlements. Water content and adjustment of soil contours also make maintenance difficult, because tomato plants have different water and humidity requirements for each type of plant. Tomato plantations are all activities that cultivate certain tomato plants on soil or other planting media in an appropriate ecosystem, to process and market goods and services produced from these plants, with the assistance of technology, capital and management to create prosperity for tomato plantation business actors. and society. Tomato plants are vegetables that we consume in this life and tomatoes can nourish our bodies. To produce quality tomato plants, good tomato plant maintenance is needed. The irrigation system that has been used so far is manual. Therefore, an automatic watering system was created using an Invertor-based Android application so that we can control watering and make it easier for tomato garden owners when they are out of town and then we can control it from Android and become more time efficient so that they can do other things.